Effects of Combined Balance and Strength Training on Measures of Balance and Muscle Strength in Older Women With a History of Falls - Zouita, Sghaier; Zouhal, Hassane; Ferchichi, Habiba; Paillard, Thierry; Dziri, Catherine; Hackney, Anthony C.; Laher, Ismail; Granacher, Urs; Ben Moussa Zouita, Amira (Frontiers in Physiology, 2020)
Objective We investigated the effects of combined balance and strength training on measures of balance and muscle strength in older women with a history of falls. Methods Twenty-seven older women aged 70.4±4.1 years (age range: 65 to 75) were randomly allocated to either an intervention (IG, n=12) or an active control (CG, n=15) group. The IG completed eight weeks combined balance and strength training programme with three sessions per week including visual biofeedback using force plates. The CG received physical therapy and gait training at a rehabilitation center. Training volumes were similar between the groups. Pre and post training, tests were applied for the assessment of muscle strength (weight-bearing squat [WBS] by measuring the percentage of body mass borne by each leg at different knee flexions [0°, 30°, 60°, 90°], sit-to-stand test [STS]), and balance. Balance tests used the modified clinical test of sensory interaction (mCTSIB) with eyes closed (EC) and opened (EO), on stable (firm) and unstable (foam) surfaces as well as spatial parameters of gait such as step width and length (cm) and walking speed (cm/s). Results Significant group x time interactions were found for different degrees of knee flexion during WBS (0.0001